NEW INSTRUMENTS FOR CHINA’S COMPETITION FOR LEADERSHIP IN THE SOUTH PACIFIC REGION (THE SPR) - Karina Igorevna Yarmoshuk (International Journal of Innovative Technologies in Social Science, 2022)
This study examines and details the new instruments the PRC is using to compete for leadership with Australia in the South Pacific region. The implications of the COVID-19 pandemic for small island states in the South Pacific are also detailed, including both health and economic risks. In conclusion the author highlights new Chinese instruments of rivalry for leadership in the South Pacific, such as: 1. Vaccine diplomacy, 2. Infrastructure projects, 3. The geopolitical strengthening of China. Although Australia as a middle power cannot economically compete with China, especially in terms of financial investments into infrastructure projects and the strength of its military power, the historically established close ties with island states, articulated shared values, broad-based development assistance and "vaccine diplomacy" are factors of Australia’s effectiveness in maintaining its leadership in the South Pacific when competing with China and maintaining the status quo in the subregion nowadays.